Abundances and host relationships of chigger mites in Yunnan Province, China. Issue 2 (20th November 2012) - ZHAN, Y.‐Z.; GUO, X.‐G.; SPEAKMAN, J. R.; ZUO, X.‐H.; WU, D.; WANG, Q.‐H.; YANG, Z.‐H.
<x xml:space="preserve">Abstract</x> This paper reports on ectoparasitic chigger mites found on small mammals in Yunnan Province, southwest China. Data were accumulated from 19 investigation sites (counties) between 2001 and 2009. A total of 10 222 small mammal hosts were captured and identified; these represented 62 species, 34 genera and 11 families in five orders. From the body surfaces of these 10 222 hosts, a total of 92 990 chigger mites were collected and identified microscopically. These represented 224 species, 22 genera and three subfamilies in the family Trombiculidae (Trombidiformes). Small mammals were commonly found to be infested by chigger mites and most host species harboured several species of mite. The species diversity of chigger mites in Yunnan was much higher than diversities reported previously in other provinces of China and in other countries. A single species of rodent, Eothenomys miletus (Rodentia: Cricetidae), carried 111 species of chigger mite, thus demonstrating the highest species diversity and heaviest mite infestation of all recorded hosts. This diversity is exceptional compared with that of other ectoparasites. Of the total 224 mite species, 21 species accounted for 82.2% of all mites counted. Two species acting as major vectors for scrub typhus (tsutsugamushi disease), Leptotrombidium scutellare and Leptotrombidium deliense, were identified as the dominant mite species in this sample. In addition to these two major vectors, 12 potential or suspected vector species were found. Most species of chigger mite had a wide range of hosts and low host specificity. For example, L. scutellare parasitized 30 species of host. The low host specificity of chigger mites may increase their probability of encountering humans, as well as their transmission of scrub typhus among different hosts. Hierarchical clustering analysis showed that similarities between different chigger mite communities on the 18 main species of small mammal host did not accord with the taxonomic affinity of the hosts. This suggests that the distribution of chigger mites may be strongly influenced by the environment in which hosts live.